2018
DOI: 10.1055/s-0038-1675788
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neutrophil Activation and Plasma DNA Levels in Patients with Pre-Eclampsia

Abstract: Pre-eclampsia (PE) is a chronic inflammatory disease in pregnancy, which is associated with enhanced blood coagulation and high thrombotic risk. To date, the mechanisms underlying such an association are not fully understood. Previous studies reported high levels of plasma deoxyribonucleic acid (DNA) in PE women, but the cellular source of the circulation DNA remains unknown. In this study, we tested the hypothesis that activated neutrophils under-going cell death, also called NETosis, maybe responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
0
32
1
1
Order By: Relevance
“…This latest observation is in agreement with the Hu et al's study showing that total plasma histones and H3 alone are increased in PE. 6 But, contrary to their results, we observed a significant change for the pregnant population compared with the nonpregnant group while they did not. This discrepancy can be explained by the fact that we analyzed samples at term of pregnancy when theirs are from around 20 weeks.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This latest observation is in agreement with the Hu et al's study showing that total plasma histones and H3 alone are increased in PE. 6 But, contrary to their results, we observed a significant change for the pregnant population compared with the nonpregnant group while they did not. This discrepancy can be explained by the fact that we analyzed samples at term of pregnancy when theirs are from around 20 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies, including our data, 4 have shown that plasma nucleosomes and cell-free DNA (cfDNA) increased during pregnancy, and that their levels were even higher in women with PMPCs, particularly in PE. 5,6 Nucleosomes are key components of neutrophil extracellular traps (NETs) and are released by neutrophil activation, a process called NETosis. 7 Aberrant NETosis has been described in PE patients.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 In a prospective study, Hu et al showed that cell-free DNA and nucleosomes were elevated in preeclampsia. 31 Our study is the first to investigate different subtypes of severe placenta-mediated complications in a prospective design, with data from non-pregnant women and from normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated NETs were stored at −80°C until further use as previously reported ( 28 ). To investigate the effect of the TME on NETs formation, neutrophils were treated using 20% plasma from the same patients with GC (n=20) or the controls (n=10) as above, following a previously described protocol ( 29 ).…”
Section: Methodsmentioning
confidence: 99%